2008
DOI: 10.1055/s-0039-1697386
|View full text |Cite
|
Sign up to set email alerts
|

Apical Extrusion of Intracanal Debris Using Two Engine Driven and Step-Back Instrumentation Techniques: An In-Vitro Study

Abstract: ObjectivesThe purpose of this study was to compare in-vitro the amount of debris extruded apically from extracted teeth, using K3, Protaper rotary instruments and manual step-back technique.MethodsForty five human single-rooted mandibular premolar teeth were randomly divided into 3 groups. The teeth in 3 groups were instrumented until reaching the working length with K3, Protaper rotary instruments and K-type stainless steel instruments with manual step-back technique, respectively. Debris extruded from the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 25 publications
1
44
0
3
Order By: Relevance
“…Therefore, apically extruded bacteria from the apical foramen could be attributed to the properties of the respective instrument used in that particular group. A previously described method was used to collect apically extruded bacteria (7)(8)(9)13). Although the vital periapical tissues are not mimicked, this technique allows a comparison of the file systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, apically extruded bacteria from the apical foramen could be attributed to the properties of the respective instrument used in that particular group. A previously described method was used to collect apically extruded bacteria (7)(8)(9)13). Although the vital periapical tissues are not mimicked, this technique allows a comparison of the file systems.…”
Section: Discussionmentioning
confidence: 99%
“…A previously described method was used to perform the test apparatus (7)(8)(9). Vials with rubber stoppers were adjusted for use by means of a heated instrument to create a hole through the center.…”
Section: Methodsmentioning
confidence: 99%
“…, Kustarci et al . ), because bacterial formation as a mature biofilm is a complex structure and is much more difficult to eliminate (Shen et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Before infection of root canals, a sterile size 15 K‐file was placed 1 mm beyond the foramen to create a hole in the nail varnish that covered the apical foramen (Kustarci et al . ). In this way, a standard size of foramen and apical patency was achieved.…”
Section: Methodsmentioning
confidence: 97%
“…The ProTaper system was also compared with K3 system (Kustarci et al 2008c, Madhusudhana et al 2010 and Mtwo (Madhusudhana et al 2010, Tasdemir et al 2010. Kustarci et al (2008c) reported that ProTaper extruded significantly more debris compared with K3, whereas Madhusudhana et al (2010) determined no significant difference. Tasdemir et al (2010), on the other hand, reported that ProTaper extruded significantly higher amount of apical debris compared with other systems tested, one of which was Mtwo.…”
Section: Extrusion Studies On Nickel-titanium Rotary Instruments (Debmentioning
confidence: 99%